2006
DOI: 10.1128/cvi.00148-06
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive and Subspecies-Specific Surface Antigen Enzyme- Linked Immunosorbent Assay for Diagnosis of Johne's Disease

Abstract: Johne's disease (JD), or paratuberculosis, caused by Mycobacterium avium subsp. paratuberculosis, is one of the most widespread and economically important diseases of livestock and wild ruminants worldwide. Control of JD could be accomplished by diagnosis and good animal husbandry, but this is currently not feasible because commercially available diagnostic tests have low sensitivity levels and are incapable of diagnosing prepatent infections. In this study, a highly sensitive and subspecies-specific enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 16 publications
(18 reference statements)
1
60
0
1
Order By: Relevance
“…36 A substantial research effort has been dedicated to the improvement and validation of diagnostic tests for JD. 2,7,9,15,23,24,26,27,31,32 Research has focused on the tests most commonly used: the enzyme-linked immunosorbent assay (ELISA) for serum antibody and culture of MAP from the feces. However, 2 challenges to evaluating diagnostic tests for JD exist that cannot easily be overcome by sampling methods or laboratory technology.…”
Section: Introductionmentioning
confidence: 99%
“…36 A substantial research effort has been dedicated to the improvement and validation of diagnostic tests for JD. 2,7,9,15,23,24,26,27,31,32 Research has focused on the tests most commonly used: the enzyme-linked immunosorbent assay (ELISA) for serum antibody and culture of MAP from the feces. However, 2 challenges to evaluating diagnostic tests for JD exist that cannot easily be overcome by sampling methods or laboratory technology.…”
Section: Introductionmentioning
confidence: 99%
“…Surface antigens of M. avium subsp. paratuberculosis (strain Linda) were extracted using 80% ethanol as previously described (8). Strain Linda, an isolate from a human patient with Crohn's disease (ATCC, Manassas, VA), resulted in more sensitive detection of antibody in JD-positive sera than in strain K-10 extracts (unpublished results).…”
Section: Methodsmentioning
confidence: 99%
“…Removal of cross-reacting antibodies by absorbing sera with Mycobacterium phlei has improved the specificity of ELISA (Yokomizo et al 1983). Some studies have reported 98.8% (Cox et al 1991), 99.7% (Reichel et al 1999) and 97.4% (Eda et al 2006) specificity, but it compromises with assay sensitivity. In general, highest sensitivity of serological tests have been recorded in animals with clinical signs of the disease since presence of antibodies is higher in the later stages of infection (Sweeney et al 1995;Nielsen & Toft 2008).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%